1990
DOI: 10.1007/bf00009929
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of several chemical indexes of soil nitrogen availability

Abstract: The ability of several chemical soil N availability indexes to predict the N supplying capability (NSC) of soils to maize in the field was evaluated in 49 field experiments over 3 years in Pennsylvania. Two recently proposed indexes based on the amount of NH4 + released by treating soil with 2 M KC1 at 100°C for 4 hr or with a pH 11.2 phosphate-borate buffer for 8 min were not good predictors of NSC (r = 0.484 and 0.254, respectively). The absorbance of a 0.01 M NaHCO 3 extract at 260 nm was also poorly correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 22 publications
1
47
1
Order By: Relevance
“…Other authors have also evaluated the present method, concluding that the amounts of N min correlated with N mineralized during the aerobic incubation of 63 soils during 24 weeks (r 2 ¼ 0.77) and with canola uptake during a greenhouse experiment (Ila'ava and Waring 1992; Jalil et al 1996). However, others have found this method to be only fairly correlated to results obtained with maize or potato crops (Hong, Fox, and Piekielek 1990;Rodrigues 2000) or several different crops grown in 123 different soils (Xu et al, 1996). The latter authors also performed aerobic incubations of the same 123 soils and once again phosphate -borate solution did not prove to be efficient in PAN prediction.…”
Section: Methods 12mentioning
confidence: 88%
See 2 more Smart Citations
“…Other authors have also evaluated the present method, concluding that the amounts of N min correlated with N mineralized during the aerobic incubation of 63 soils during 24 weeks (r 2 ¼ 0.77) and with canola uptake during a greenhouse experiment (Ila'ava and Waring 1992; Jalil et al 1996). However, others have found this method to be only fairly correlated to results obtained with maize or potato crops (Hong, Fox, and Piekielek 1990;Rodrigues 2000) or several different crops grown in 123 different soils (Xu et al, 1996). The latter authors also performed aerobic incubations of the same 123 soils and once again phosphate -borate solution did not prove to be efficient in PAN prediction.…”
Section: Methods 12mentioning
confidence: 88%
“…This method was described by Hong, Fox, and Piekielek (1990). A 3-g wet sample was added to 20 mL of 2 M KCl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these lab-based measures of soil N mineralization are well correlated with field-based measures of soil N supply (Hong et al 1990;Beauchamp et al 2004;Sharifi et al 2007b). Mulvaney et al (2005) and Williams et al (2007) demonstrated the potential to use the ISNT to make fertilizer N recommendations for corn whereas Klapwyk and Ketterings (2006) found that the ISNT needed to be used in combination with soil organic matter content.…”
Section: Soil-based Diagnostic Testsmentioning
confidence: 99%
“…Thus, the higher the level of soil organic matter the higher the estimates of soil N availability. This approach has as a main limitation the fact that the organic matter is not necessarily a reliable soil N availability index [11,15,17,21]. On the other hand, several annual crops (winter wheat, rye, maize, sunflower, potato,…) are cultivated in inland regions of Portugal with or without irrigation on soils with low levels of organic matter.…”
Section: Introductionmentioning
confidence: 99%